Enterobiasis y Ascariasis en un orfanato de Lima. Tratamiento masivo con dosis única de pamoato de pirantel - Lumbreras, Hugo (2024)
We report the results of mass treatment, with respect to Enterobius vermicularis and Ascaris lumbricoides of 1,627 people in a Lima orphanage, with a single oral dose of pyrantel pamoate.  A sample of 417 children was chosen at randon to provide confidence limits of over 95%; th GRAHAM scotch tape technique, adequate to detection of Enterobius ova, was performed twice botton before and after treatment in 386 of the selected children; 369 children provided fecal samples which were studied by the following techniques: Direct motile larvae and protozoa), and Rapid Sedimentation (for dense ova, such as Fasciola hepatica); other children failed to provide either the pre-post-treatment samples. E. vermicularis ova were found in 249 (64.5%) of the 386 children. A. lumbricoides ova were found in 22 of the 369 children. ´Pyrantel pamoate, as a suspension, and at a dose of 10mg per kg body weight, was given in a single da to all people connected with the orphanage. Parasito logical controls, using the same techniques, were perfomed between 7 and 26 days after, the GRAHAM technique being repeated twice within this period for each child. E. Vermicularis ova were found in 231 children (92.8%) of the 249 first found infested; of the 2 parasitized by A. lumbricoides 21 (95.5%) had were reported in the population subjected to treatment.  Other reports are reviewed and compared with the present one, and comments made on the advantages of pyrantel pamoate: wide antihelminthi spectrum, easy one-dose oral administration, abscense of secondary effects, and superiority over similar drugs.